Self-reported anxiety in first-year medical students at the University of Zaragoza during the COVID-19 confinement - Santabárbara, Javier; Saravia-Bartra, María M.; López-Antón, Raúl; Serreta, Pablo; Bueno-Notivol, Juan (Spanish Journal of Medical Education, 2022)
Aims: The aim of this study is to determine the proportion of anxiety in Spanish medical students during the COVID-19 pandemic. Methodology: 31 undergraduate medical students from a Spanish university answered an on-line questionnaire in April 2020. The GAD-7 scale was used to measure anxiety levels, and the presence of probable anxiety was calculated with cut-off points. Results: Anxiety was observed in 64.5% of the sample, being more common among women and younger students. Conclusions: The proportion of anxiety found in the sample highlight the urgent need to evaluate anxiety symptomatology in medical students during the COVID-19 pandemic and to stablish adequate psychological support programs. Future epidemiological studies with large and representative samples are warranted to surveille mental health in this population.